SINTESIS KATALIS CuO-ZEOLIT ALAM UNTUK REAKSI REDUKSI GAS NO2 MENGGUNAKAN REDUKTOR SENYAWA HIDROKARBON - Arif Hidayat; Sutarno Sutarno (Faculty of Industrial Technology Universitas Islam Indonesia, 2013)
The exhaust gases from automobile engines and industrial boilers contain mainly oxides of carbon (CO and CO2), oxides of nitrogen (NOx), hydrocarbons (HC), sulphur dioxide (SO2), particulates and soot. One of the most urgent problems is removal of NOx, typically produced during high-temperature combustion and contribute to formation of smog and ground-level ozone by reacting with hydrocarbons in presence of sunlight. Preparation, and modification of CuO / natural zeolite as well as their characterizations had been carried out. The aim of this research is to prepare the best characters catalyst for selective catalytic reduction of NOx. The CuO / natural zeolite was prepared by mechanically mixing of 100 g of natural zeolite, which it has been heated at 400oC, with CuNO3.3H2O powder, The weight ratio of the mixture was 2.5 and 5% (w/w). The mixture was then calcined at 400oC for 6 hours. The calcined product was characterized using X-Ray Diffractometry, X-Ray Fluorescence analysis and Gas Sorption Analysis methods to determine its physicochemical properties changes caused by mixing and calcination. The characterization results showed that dispertion of CuNO3.3H2O on zeolite resulted in the increasing of copper concentration on CuO / natural zeolite. The concentration of Cu on natural zeolite was found to be 0.15% (w/w), meanwhile on CuO / natural zeolite was 2.29% (w/w). From X-Ray Diffractometry analysis result no information was found that CuO was dipersed on natural zeolite. It was caused by overlapping of the reflections of zeolite with reflections of CuO. On the otherhand, the gas sorption analysis result exhibited that the dispersion of CuO on zeolite resulted in the decreasing of total pore volume as well as specific surface area of the natural zeolite. The specific surface areas of natural zeolite and CuO / natural zeolite were 228,1 and 172,1 m2/g, respectively, meanwhile the total pore volumes of natural zeolite and CuO / natural zeolite were 0.2316 and 0.2108 m3/g